Depression of Guanosine Diphosphate-Mannose Pyrophosphorylase by Mutations in Two Different Regulator Genes Involved in Capsular Polysaccharide Synthesis in Escherichia coli K-12 - Lieberman, Michael M. (1970)
Mutations in a regulator gene (capR) that causes increased synthesis of capsular polysaccharide and derepressed synthesis of several enzymes involved in polysaccharide synthesis also derepress synthesis of guanosine diphosphate (GDP)-mannose pyrophosphorylase. In addition, a second mucoid mutation (capS, which maps separately from capR) also results in the derepression of GDP-mannose pyrophosphorylase. New conditions for assaying GDP-mannose hydrolyase and GDP-l-fucose synthetase permitted us to show that these enzymes are also derepressed in the capS mucoid strain. Although phosphomannose isomerase and uridine diphosphate-galactose-4-epimerase are derepressed in capR mucoid strains, they are not derepressed in capS mucoid strains. A nonmucoid mutant of a strain containing the capR9 (mucoid) allele was deficient in GDP-mannose pyrophosphorylase.